Pengaruh Lingkungan Kerja dan Sistem Manajemen Keselamatan Kesehatan Kerja terhadap Kecelakaan Kerja (Studi Kasus Di Ruang IGD RSUP dr. Hasan Sadikin, Bandung) - Tatang Adi Permana (Jurnal Syntax Transformation, 2021)
Several things that affect the level of work accidents, one hich is the work environment and occupational health safety management system (SMK3). study aims to analyze the work environment, K3 management and work accidents to analyze the influence of the work environment and K3 management on work accidents in the Emergency Room of the Central Hospital dr. Hasan Sadikin Kota Bandung partially or simultaneously The sample used cluster random sampling, amounting to seven eople who came from medical personnel, health workers and non-medical personnel Data collection tec ues are carried out through observation, questionnaires and interviews. The research method used is descriptive and verification, which describes the influence of two or more different variables according to the facts. The result shows that the work environment variable according to the respondent's assessment is in the sufficient category, then the SMK3 variable according to the r ondent's assessment is in the sufficient category, and the incidence of work accidents is low. The results of the t-test for the work environment and SMK3 variables showed that it had no effect on work accidents in the ergenc y room of dr. Hasan Sadikin Kota Bandung, as well as the results of the f test stated that there was no significant relationship between the emergency room and the work environment, SMK3 and work accidents at the Central General Hospital dr. Hasan Sadikin City of Bandung.